The potential role of free chitosan in bone trauma and bone cancer management - Tan, M.; Shao, P.; Friedhuber, A.; van Moorst, M.; Elahy, M.; Indumathy, S.; Dunstan, D.; Wei, Y.; Dass, Crispin (Elsevier Ltd, 2014)
Bone defects caused by fractures or cancer-mediated destruction are debilitating. Chitosan is commonly used in scaffold matrices for bone healing, but rarely as a free drug. We demonstrate that free chitosan promotes osteoblast proliferation and osteogenesis in mesenchymal stem cells, increases osteopontin and collagen I expression, and reduces osteoclastogenesis. Chitosan inhibits invasion of endothelial cells, downregulating uPA/R, MT1-MMP, cdc42 and Rac1. Better healing of bone fractures with greater trabecular bone formation was observed in mice treated with chitosan. Chitosan induces apoptosis in osteotropic prostate and breast cancer cells via caspase-2 and -3 activation, and reduces their establishment in bone. Chitosan is pro-apoptotic in osteosarcoma cells, but not their normal counterpart, osteoblasts, or chondrosarcoma cells. Systemic delivery of chitosan does not perturb angiogenesis, bone volume or instinctive behaviour in pregnant mice, but decreases foetal length and changes pancreatic secretory acini. With certain controls in place, chitosan could be useful for bone trauma management.